Digital systems principles and applications - Tocci, Ronald J. (Pearson Prentice Hall, 2004)
[This text] is a comprehensive study of the principles and techniques of modern digital system. It teaches the fundamental principles of digital systems and covers thoroughly both the traditional and the most modern methods of applying digital design and development techniques, including how to manage a systems-level project. [It] is intended for use in two- and four-year programs in technology, engineering, and computer science.